Interlaboratory comparison of fig (Ficus carica L.) microsatellite genotyping data and determination of reference alleles - Matjaž HLADNIK; Jernej JAKŠE; Bouchaib KHADARI; Sylvain SANTONI; Dunja BANDELJ (Acta Agriculturae Slovenica)
Microsatellites have been identified as the marker of choice in plant genotyping projects. However, due to length discrepancies obtained between different laboratories for the same allele, interlaboratory comparison of fingerprinting results is often a difficult task. The objectives of this study were to compare genotyping results of two laboratories, to evaluate genetic parameters of microsatellite markers and to determine reference allele sizes for fig cultivars from the Istrian peninsula.